KONSEP ARSITEKTUR ISLAMI SEBAGAI SOLUSI DALAM PERANCANGAN ARSITEKTUR - Edrees, Munichy Bachroon (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2010)
In many Qur’anic verses and Hadith, the term ‘to construct’ or ‘to build’ is frequently mentioned. It means that there are some principles in this kind of activity in Islam, that can be called Islamic principal of architecture. Therefore, it is very important for Muslim architects to have a deep understanding about these principals, and to bring them to the operational level. Basically, to build it to make some social, technical, economical, and psychological arrangements. Great changes that occur within the relationship of human and their environment in fact influence the way architects deal with these arrangements. Islamic principal of architecture give Muslim architects a basis in their architectural activities that derived from the Qur’an and Hadith. Based on these principals, the arrangements will have to considerate hablumminallah, hablumminannaas, and hablumminal’alam, which are the core of the Islamic relationships. The result of these arrangements then could be applied in five important things in architecture: function, form, technology, safety, and comfort, with a deep consideration in contextuality and eficiency.